Transcription activity of the signalling pathway genes of VEGFR-2 in cervical cancer determined with the oligonucleotide microarray technique - Banyś, Anna; Orchel, Joanna; Mazurek, Urszula; Michalski, Bogdan; Drosdzol, Agnieszka; Skrzypulec, Violetta; Jankowski, Andrzej (Menopause Review/Przegląd Menopauzalny, 2009)
Neoplastic transformation is a consequence of multiple rather than single gene dysfunction. Whole sets of genes controlling various metabolic and regulatory pathways of a cell are involved. The aim of the study was to indicate the genes for proteins of the signalling pathways for VEGFR-2, as playing a main role in neoplastic angiogenesis; their transcription activity significantly differs in biopsy samples from histologically normal epithelium and squamous cell cervix. The gene expression profile was assigned using oligonucleotide microarrays of HU 133A (by Affymetrix), enabling analysis of 22283 mRNA transcripts, of which 128 were selected for the study, as taking part in VEGFR-2-activated signalling pathways. After normalization of the results with RMA Express software, three different methods were applied to identify the differentiating genes for squamous cell carcinoma. According to the results, irrespective of the applied method, VEGFA and Spk1 are specific genes differentiating.